SISTEM INFORMASI CUSTOMER RELATIONSHIP MANAGEMENT PADA RESTORAN DI KOTA MATARAM - Choirunnisa, Valia Adri; Alamsyah, Noor; Irmawati, Budi (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2023)
Internet technology has a significant impact, especially for online restaurant businesses that require a restaurant management information system, known as CRM (Customer Relationship Management) system. The case study used in developing the CRM system for Valia's Kitchen. Valia's Kitchen is an online restaurant business that has been operating in the culinary industry since 2019, located in the city of Mataram. Valia's Kitchen has partnered with a ride-hailing company and provides its own application. However, there are limitations and shortcomings in the operational management provided, such as the inability to display customer data such as names and contact numbers due to privacy and security concerns, the inability to back up all order data, lack of inventory management for products and raw materials, and the absence of a cash flow record for expenditure and income over a specific period, leading to limitations in operational management features. To address these issues, the researchers designed a CRM Information System for Restaurants in the city of Mataram to improve operational efficiency and facilitate transactions with customers. The system is web-based, built using PHP programming language with a MySQL database, following the Personal Extreme Programming (PXP) development methodology, and tested using black box testing approach. The implementation of CRM in the system is manifested in features such as customer data management, menu management, raw material management, promotions management, partner management, raw material purchasing, restaurant expenses management, cash flow recording, transaction reports, restaurant statistics, and detailed reviews. The Black Box Testing results showed that the system features were functioning well without any errors. Furthermore, the User Acceptance Testing (UAT) results indicated that the average assessment scores for three admin respondents were 82%, while the average assessment scores for eleven respondents on the customer side were 86%.